Analisis Fluktuasi Partisipasi Penggemar K-Pop Melalui Platform Digital: Studi Kasus Penggunaan Aplikasi Weverse - Yenisya Rama Pragiyasti; Arif Surya Kusuma (Faculty of Social and Political Sciences, Universitas Singaperbangsa Karawang, Indonesia, 2025)
This study is motivated by the increasing interaction between fans and K-Pop artists on digital platforms, especially Weverse, which is designed as an exclusive media by HYBE Corporation. The purpose of the study is to analyze SEVENTEEN fans' participation in Weverse and identify the factors that influence it. Using a qualitative descriptive approach with McLuhan's Law of Media theory and ecological media as the analytical framework, data were collected through in-depth interviews with four active paying and non-paying fans who have interacted on Weverse for at least the past six months. The interview technique was conducted directly and analyzed using the Miles and Huberman interactive model. The results show that fan participation is influenced by artist activity, access to exclusive content, and fandom community dynamics. Non-paying fans tend to be more active in public interactions than paying users. This study contributes to the study of digital media and participatory culture by highlighting how access structures in digital platforms affect fan interaction patterns. The novelty of this study lies in the focus of the analysis on the differentiation of participation based on collection status, which has not been widely explored in the context of community-based platforms such as Weverse. Keywords: Participation Fluctuation, Social Capital, Kpop, Law of Media, Weverse